Analisis Kesulitan Calon Guru Matematika dalam Menyelesaikan Soal Olimpiade Bidang Aljabar - Pradanti, Paskalia; Agustyaningrum, Nina (Universitas Islam Jember, 2024)
Mathematics Education Undergraduate Study Program students as prospective teachers need to be prepared with good competencies so that they are ready to carry out the Olympic preparation program when they are already in the profession as teachers. Therefore, research will be carried out that aims to analyze the difficulties of prospective mathematics teacher students in solving Olympiad questions, which are the basis for designing Olympiad learning in higher education. This research was carried out with students from the VII-semester Mathematics Education Study Program at a university in Magelang using a qualitative approach. Data obtained through written assessments and interviews were then analyzed to identify difficulties in understanding concepts, difficulties in applying principles, and difficulties in solving verbal problems experienced by the subjects. The results of the data analysis show that these three types of difficulties were found in the steps for solving olympiad questions in algebra. Keywords: difficulty analysis, prospective mathematics teacher, mathematics olympiad